2005
DOI: 10.1111/j.1468-1293.2005.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and costs associated with dyslipidaemia and related conditions in HIV‐infected patients: a retrospective cohort study

Abstract: Metabolic abnormalities are common in HIV-infected individuals and, although multifactorial in origin, have been strongly associated with antiretroviral therapy. MethodsUsing automated claims and clinical databases, combined with medical record data, we evaluated the burden of dyslipidaemia (DYS) and associated metabolic abnormalities among a cohort of 900 HIV-infected patients aged 18 years and older who received their care from a large multispecialty medical group between 1 January 1996 and 30 June 2002. A C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
(33 reference statements)
4
19
0
1
Order By: Relevance
“…In the D:A:D study, rates of dyslipidaemia remained relatively stable for each calendar year between 2000 and 2006, 5 while data from the Veteran's Affair study reported dyslipidaemia to be more common among older HIV-positive patients who are also male and of white ethnicity. 49 As this population is living longer, HIV-positive patients will be receiving cART for much longer, and the independent effect of aging on dyslipidaemia will continue to be confounded by the direct effect of ART, other CVD risk factors and increases in the use of lipid-lowering medication.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…In the D:A:D study, rates of dyslipidaemia remained relatively stable for each calendar year between 2000 and 2006, 5 while data from the Veteran's Affair study reported dyslipidaemia to be more common among older HIV-positive patients who are also male and of white ethnicity. 49 As this population is living longer, HIV-positive patients will be receiving cART for much longer, and the independent effect of aging on dyslipidaemia will continue to be confounded by the direct effect of ART, other CVD risk factors and increases in the use of lipid-lowering medication.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…In Malaysia there were more than 80 000 [52 000-120 000] On the other hand, ART (Antiretroviral Therapy) can cause a variety of side effects, some of them adversely affecting the nutritional status of PLHIV (WHO, 2007). Changes in body composition and metabolic complications such as dyslipidemia, insulin resistance Richter et al, 2005;Hansen et al, 2009) and increased rate of cardiovascular disease (CVD) (Depairon et al, 2001;Baum et al, 2006;Sankatsing et al, 2009) are the most commonly quoted adverse nutritional effects on patients receiving highly active antiretroviral therapy (HAART). Related to this, abdominal obesity as a typically morphological abnormality has been observed among both HIV-positive men and women (Galli et al, 2003;Jaime et al, 2006) in many countries where HAART has been available for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a growing body of literature shows that HCV infection has been associated with lower rates of HIV-and highly active antiretroviral therapy (HAART)-associated dyslipidaemias among HIVinfected patients, with lower mean total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) [10,[15][16][17][18][19][20][21]. Also, patients with chronic HCV monoinfection have lower rates of lipid abnormalities than age-and sex-matched healthy subjects [22], and LDL-C concentrations were inversely correlated with the severity of liver disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among HIV-infected patients, HCV coinfection has been shown to be associated with higher rates of several metabolic complications including lipodystrophy [10], hepatic steatosis and nonalcoholic fatty liver disease (NAFLD) [11], metabolic syndrome [12], glucose intolerance and diabetes [13,14]. Conversely, a growing body of literature shows that HCV infection has been associated with lower rates of HIV-and highly active antiretroviral therapy (HAART)-associated dyslipidaemias among HIVinfected patients, with lower mean total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) [10,[15][16][17][18][19][20][21]. Also, patients with chronic HCV monoinfection have lower rates of lipid abnormalities than age-and sex-matched healthy subjects [22], and LDL-C concentrations were inversely correlated with the severity of liver disease [23].…”
mentioning
confidence: 99%